The natural killer–activating receptor, NKG2D, on CD3+CD8+ T cells plays a critical role in identifying and killing autologous myeloma cells. Issue 6 (22nd January 2014) - Talebian, Laleh; Fischer, Dawn A.; Wu, Jillian; Channon, Jacqueline Y.; Sentman, Charles L.; Ernstoff, Marc S.; Meehan, Kenneth R.
<x xml:space="preserve">Abstract</x> Background The NKG2D receptor, one of the natural killer (NK) cell–activating receptors, is expressed on the surface of CD3+CD8+ T cells, γδ+ T cells, NK cells, NKT cells, and a few CD4+ T cells. We show, for the first time, a critical role for the NKG2D receptor on CD3+CD8+ T cells isolated from myeloma patients, in identifying and killing autologous myeloma cells isolated from the same patients' marrow. We also show that blocking NKG2D using anti‐NKG2D reverses the cytotoxicity while blocking HLA‐I using antibodies does not have the same effect, showing that the autologous cytotoxicity is NKG2D dependent and major histocompatibility complex (MHC)‐I independent. We further confirmed the NKG2D specificity by small interfering RNA (siRNA) down regulation of NKG2D receptor. Study Design and Methods Using ex vivo expansion methods that enrich for NKG2D+CD3+CD8+ T cells, we investigated whether these ex vivo expanded NKG2D+CD3+CD8+ T cells would recognize and lyse autologous and allogeneic myeloma cells, independent of T‐cell receptor or MHC‐I expression. Results Myeloma cell lysis by the NKG2D+CD3+CD8+ T cells correlated with the amount of NKG2D ligand expression. With receptor–ligand interaction, interferon‐γ and tumor necrosis factor‐α were released. Blocking the NKG2D receptor by using either monoclonal antibodies or siRNAs inhibited the receptor's function and prevented myeloma cell lysis. Conclusion Clinical trials are ongoing to determine a correlation with the number and function of NKG2D+CD3+CD8+ T cells and clinical outcomes in transplanted myeloma patients, including lymphocyte recovery following transplant and overall survival.